Climate change undermines the global functioning of marine food webs. (10th January 2020) - du Pontavice, Hubert; Gascuel, Didier; Reygondeau, Gabriel; Maureaud, Aurore; Cheung, William W. L.
Abstract: Sea water temperature affects all biological and ecological processes that ultimately impact ecosystem functioning. In this study, we examine the influence of temperature on global biomass transfers from marine secondary production to fish stocks. By combining fisheries catches in all coastal ocean areas and life‐history traits of exploited marine species, we provide global estimates of two trophic transfer parameters which determine biomass flows in coastal marine food web: the trophic transfer efficiency (TTE) and the biomass residence time (BRT) in the food web. We find that biomass transfers in tropical ecosystems are less efficient and faster than in areas with cooler waters. In contrast, biomass transfers through the food web became faster and more efficient between 1950 and 2010. Using simulated changes in sea water temperature from three Earth system models, we project that the mean TTE in coastal waters would decrease from 7.7% to 7.2% between 2010 and 2100 under the 'no effective mitigation' representative concentration pathway (RCP8.5), while BRT between trophic levels 2 and 4 is projected to decrease from 2.7 to 2.3 years on average. Beyond the global trends, we show that the TTEs and BRTs may vary substantially among ecosystem types and that the polar ecosystems may be the most impacted ecosystems. The detected and projected changes in mean TTE and BRT will undermine food web functioning. Our study provides quantitative understanding of temperature effects on trophodynamic of marine ecosystems under climate change. Abstract : We examine the influence of temperature on global biomass transfers from marine secondary production to fish stocks in coastal marine food web by combining fisheries and life‐history traits of exploited marine species. We find that biomass transfers in tropical ecosystems are less efficient and faster than in areas with cooler waters. Furthermore, we project that the mean trophic transfer efficiency is expected to decrease between 2010 and 2100, whereas biomass residence time (BRT) is projected to decrease. Beyond the global trends, we show that the trophic transfer efficiencies and BRTs vary substantially among ecosystem types.